2017
DOI: 10.1002/pssa.201700563
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐TMDC‐Graphene Hybrid Plasmonic Metasurface for Enhanced Biosensing: A Theoretical Analysis

Abstract: In this work, a plasmonic metasurface for ultra‐sensitive biosensing based on graphene‐transition metal dichalcogenide (TMDC)‐graphene hybrid nanostructures are designed. The coating of the two‐dimensional nanosheets plays an important role for the sensitivity enhancement of the biosensors at the atomic scale. To achieve the maximum plasmon resonance energy transfer, different parameters of the hybrid nanostructures are systematically investigated including the material types and the number of TMDC layers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Benefiting from these advantages, TMDCs offer a unique platform for investigation of intriguing light-matter interactions at the nanoscale through, besides the well-known van der Waals heterostructures 12,13 , the integration with artificial materials, such as photonic nanocavities 14,15 , plasmonic nanostructures 16 , and single nanoparticle antennas 17 . This enables the establishment of compact optoelectronic devices, including tunable light emitters 18 , nanolasers 19,20 , electro-optic modulator 21 , optical switches 22 , biosensors/detectors 23,24 , fieldeffect transistors 25 , quantum devices 26 , etc., which are the key elements of the next-generation integrated photonic circuits. Recently, TMDCs implemented in plasmon-exciton hybrid systems have been intensively explored, such as giant Rabi splitting 27,28 , multifold enhancement in PL 29,30 and active control of plasmon-exciton coupling 31,32 in various noble metal-TMDC hybrid nanostructures.…”
mentioning
confidence: 99%
“…Benefiting from these advantages, TMDCs offer a unique platform for investigation of intriguing light-matter interactions at the nanoscale through, besides the well-known van der Waals heterostructures 12,13 , the integration with artificial materials, such as photonic nanocavities 14,15 , plasmonic nanostructures 16 , and single nanoparticle antennas 17 . This enables the establishment of compact optoelectronic devices, including tunable light emitters 18 , nanolasers 19,20 , electro-optic modulator 21 , optical switches 22 , biosensors/detectors 23,24 , fieldeffect transistors 25 , quantum devices 26 , etc., which are the key elements of the next-generation integrated photonic circuits. Recently, TMDCs implemented in plasmon-exciton hybrid systems have been intensively explored, such as giant Rabi splitting 27,28 , multifold enhancement in PL 29,30 and active control of plasmon-exciton coupling 31,32 in various noble metal-TMDC hybrid nanostructures.…”
mentioning
confidence: 99%
“…1a, b. This process is insignificant at a metal-low-index interface [17,18] due to the high barrier; however, it could be large at a metal-high-index interface and could lead to intensified energy of surface plasmon and narrowed absorption spectrum [18,19]. This process could also promote larger electric field enhancement at the sensing interface thereby resulting in a higher SPR sensitivity to the target analytes.…”
Section: Interface Dipole Contribution In the Resulting Plasmonic Fieldmentioning
confidence: 99%
“…It was found that coating of a 45-nm Au thick film by 3-layer MoS 2 and a monolayer graphene reduces the width of the SPR curve and provides phase sensitivity enhancement about two orders of magnitude as compared to Au/graphene SPR systems [15]. To achieve the maximum sensitivity in this structure, materials and the number of transition metal dichalcogenide (TMD) layers have been optimized [16,17]. It was found that adding several layers of TMDs on the top of noble metal films improves electric field enhancement at the sensing interface (graphene in this case) and leads to improved sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Current trends in SPR technology directed towards improving the sensitivity and accuracy of measurements with the application of multilayer graphene or Molybdenum disulfide (MoS 2 ) coating, wear resistance of the sensitive element and developing methods for regeneration of receptors for multiple use [19][20][21]. SPR imaging with integrated Microfluidics lab-on-a-chip (LOC) for point-of-care (POC) application in medical and clinical theranostics appears to be the promising technology of near future [22].…”
Section: History Of Spr Technologymentioning
confidence: 99%